2014
DOI: 10.1063/1.4862181
|View full text |Cite
|
Sign up to set email alerts
|

Current loss due to recombination in Cu-rich CuInSe2 solar cells

Abstract: The absorbers in Cu(In,Ga)Se2 solar cells in general are Cu-poor. However, better transport properties and lower bulk recombination in “Cu-rich” material led us to develop “Cu-rich” CuInSe2 solar cells. We expect higher diffusion lengths and better carrier lifetimes for “Cu-rich” CuInSe2 solar cells, resulting in a higher short circuit current of “Cu-rich” solar cells, compared to Cu-poor ones. However, recent investigations show that the current is lower for absorbers grown under Cu-excess compared to Cu-poor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 23 publications
4
36
0
1
Order By: Relevance
“…10 The Cu/In ratios measured by energy-dispersive X-ray spectroscopy (EDX) were 0.9 and 1.3 for Cu-poor and Cu-rich absorbers, respectively. After the deposition, a 10% aqueous solution of Potassium Cyanide (KCN) was applied to Cu-rich absorbers for 5 min in order to remove the secondary copper selenide phases followed by a potassium fluoride (KF) surface treatment performed in the MBE system for the sample labelled "Cu-rich þ KF" as described in Ref.…”
mentioning
confidence: 99%
“…10 The Cu/In ratios measured by energy-dispersive X-ray spectroscopy (EDX) were 0.9 and 1.3 for Cu-poor and Cu-rich absorbers, respectively. After the deposition, a 10% aqueous solution of Potassium Cyanide (KCN) was applied to Cu-rich absorbers for 5 min in order to remove the secondary copper selenide phases followed by a potassium fluoride (KF) surface treatment performed in the MBE system for the sample labelled "Cu-rich þ KF" as described in Ref.…”
mentioning
confidence: 99%
“…Possible is also neutralisation with other defect types that have not been observed in the neutron scattering study, like anion related defects. In Cu-poor Cu(In,Ga)Se 2 thin films the presence of Na is essential to reach sufficient doping levels [6,80,82]. Neutron diffraction studies show that the addition of Na leads to a decrease of In Cu antisite donors [83], which can explain the increase in p-type doping with the addition of Na.…”
Section: à3mentioning
confidence: 99%
“…77 While record CISe devices have a Cu-poor final composition, 78 they often include a Cu-rich growth step that is observed to enhance optoelectronic and structural properties. 79 Our group 67 also measured a narrower 112 XRD peak for laser annealed absorbers from Cu-rich precursors when compared to their Cu-poor counterparts. Mooney and Hermann 80 revealed that the extinction coefficient, k, which describes the attenuation of electromagnetic radiation by a material, is dependent on stoichiometry and ranged from 0.15 for Cu-poor to 0.3 for Cu-rich electrodeposited precursors.…”
Section: Annealing Of Co-deposited Cu-in-sementioning
confidence: 99%